Frequency of a natural truncated allele of MdMLO19 in the germplasm of Malus domestica - Pessina, Stefano (Mol Breed, 2017)
Podosphaera leucotricha is the causal agent of powdery mildew (PM) in apple. To reduce the amount of fungicides required to control this pathogen, the development of resistant apple cultivars should become a priority. Resistance to PM was achieved in various crops by knocking out specific members of the MLO gene family that are responsible for PM susceptibility (S-genes). In apple, the knockdown of MdMLO19 resulted in PM resistance. However, since gene silencing technologies such as RNAi are perceived unfavorably in Europe, a different approach that exploits this type of resistance is needed. This work evaluates the presence of non-functional naturally occurring alleles of MdMLO19 in apple germplasm. The screening of the re-sequencing data of 63 apple individuals led to the identification of 627 single nucleotide polymorphisms (SNPs) in five MLO genes (MdMLO5, MdMLO7, MdMLO11, MdMLO18, and MdMLO19), 127 of which were located in exons. The T-1201 insertion of a single nucleotide in MdMLO19 caused the formation of an early stop codon, resulting in a truncated protein lacking 185 amino acids, including the calmodulin-binding domain. The presence of the insertion was evaluated in 115 individuals. It was heterozygous in 64 and homozygous in 25. Twelve of the 25 individuals carrying the insertion in homozygosity were susceptible to PM. After barley, pea, cucumber, and tomato, apple would be the fifth species for which a natural non-functional mlo allele has been found. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11032-016-0610-8) contains supplementary material, which is available to authorized users.